What next for Al-Qaeda - Jenkins, Paul ([Australia] : BBC, 2006)
Award winning reporterm Peter Taylor's last series, New Al-Qaeda, was uncannily prophetic. Its three programmes were completed the day before the London bombongs of 7 July and transmitted in their wake. With this and the previous 2004 series, The Third World War Al-Qaeda, Taylor and his team have an unprecedented television track record in covering one of the most important stories of our time.
Ep. 1. Time to talk? - Ep. 2. Turning the terrorist.
Title from container
Executive producer, Fiona Stourton
dvd format.
Keywords: Qaida (Organization).; Terrorism